Efficient delivery of chlorin e6 into ovarian cancer cells with octalysine conjugated superparamagnetic iron oxide nanoparticles for effective photodynamic therapy. Issue 47 (21st November 2016) - Zhao, Li; Yang, Hongkuan; Amano, Tsukuru; Qin, Hongmei; Zheng, Luyi; Takahashi, Akimasa; Zhao, Shiguang; Tooyama, Ikuo; Murakami, Takashi; Komatsu, Naoki
Abstract : Chlorin e6, loaded on the surface of SPION-PG-Lys8 through electrostatic attraction, was delivered preferentially into mitochondria of SKOV3 ovarian cancer cells, improving efficacy of photodynamic therapy significantly. Abstract : In cancer treatment, efficient delivery of active anticancer drugs into cancer cells is highly desirable for maximizing therapeutic effects and alleviating side effects. In this work, a nanocarrier consisting of an Fe3 O4 core, a polyglycerol coating, and an octalysine functionality (SPION-PG-Lys8 ) has been designed, synthesized and used to deliver a photosensitizer, chlorin e6 (Ce6), into cancer cells for photodynamic therapy (PDT) of cancer cells. SPION-PG-Lys8 is colloidally stable in various aqueous solutions, showing a high positive zeta potential of 47.2 ± 6.9 mV in pure water. In vitro characterization reveals that SPION-PG-Lys8 is efficiently taken up by SKOV3 ovarian cancer cells, exhibiting low cytotoxicity, and suppressed autophagy compared to bare SPIONs. Negatively charged Ce6 is thus loaded on the SPION-PG-Lys8 through electrostatic attraction to yield a SPION-PG-Lys8 /Ce6 nanocomplex with a positive zeta potential of 22.4 ± 4.3 mV. SPION-PG-Lys8 /Ce6 is more easily taken up by the cells than free Ce6, and surprisingly, the internalized SPION-PG-Lys8 /Ce6 is found to be enriched in the mitochondria. SPION-PG-Lys8 /Ce6 exhibits almost no cytotoxicity under dark conditions, but strong photocytotoxicity due to the light-triggered production of reactive oxygen species (ROS) destroying the mitochondria. Taken together, our results highlight the great potential of SPION-PG-Lys8 as an efficient carrier of Ce6 for photodynamic cancer therapy.